Parental experiences with behavioural problems in Smith–Magenis syndrome: The need for syndrome-specific competence. (September 2019) - Nag, Heidi Elisabeth; Hoxmark, Lise Beate; Nærland, Terje
The experience of having a rare disorder was summarised in a large study as 'falling outside the vast field of knowledge of the professionals'. Parents (31 mothers and 17 fathers) of 32 persons with Smith–Magenis syndrome (SMS) participated in this study. A phenomenological approach was used to analyse the data into topics and themes. Four themes emerged: behavioural challenges displayed, parents' strategies for meeting the challenging behaviours, parents' experiences of their own competence and parents' experiences of professionals' competence and understanding regarding children with SMS and their behaviour challenges. We found that parents of children with SMS experience that they are exposed to severe challenging behaviours from their child. The parents believe that they experience more misunderstandings with professionals and that the challenging behaviours increase because there are some specific characteristics of SMS that professionals are not aware of or do not consider in their support services.